Implementasi Kebijakan Transportasi Laut dalam Rangka Pengembangan Sistem Logistik Nasional - Kundori Kundori; pranyoto pranyoto (Majalah Ilmiah Bahari Jogja, 2023)
This study aims to analyze the implementation of sea transportation policies in the context of developing a national logistics system in the long term which is expected to be able to contribute to overcoming various sea transportation problems, especially those related to the development of a national logistics system. The research design uses a literature review with a qualitative descriptive method. Secondary data sources were obtained from the results of research that had been carried out by previous researchers. The strategy undertaken to implement the development of a national logistics system is to link all logistics system activities locally, nationally and globally in order to achieve national competitiveness at the regional and global levels in order to improve people's welfare by reducing logistics costs, expediting the distribution of goods, improving logistics services so that Guaranteed availability of staple goods that are easily accessible. The national logistics system can increase investment in the regions, especially to increase added value as return cargo, as well as strengthen sovereignty in Indonesia's border areas